The initial clinical-functional state of patients with excessive body weight and obesity upon admission to the outpatient-polyclinic stage of treatment - Lysenko, T. V. (Journal of Education, Health and Sport, 2017)
When examining 125 patients with excessive body weight and obesity, when entering the out-patient-polyclinic stage of treatment, subjective (prevailing complaints of excess weight, the cardiovascular and nervous system, musculoskeletal system) and objective (weight gain, BMI, WC, increased appetite, cravings for sweets, eating disorders) symptoms, changes in the functional state of the nervous system (asthenoneurotic syndrome was registered) and cardiovascular (elevated pressure, signs of disturbance of myocardial repolarization, left ventricular hypertrophy, disturbance of intracardiac and systemic hemodynamics) system, biochemical (disturbance of the lipid spectrum of blood and fasting blood glucose), and quality of life. More pronounced changes were in patients with obesity of II and III stages. The data obtained form the basis for the development of a program for the prevention and treatment of patients at the outpatient and polyclinic stage using basic, drug therapy and physical factors.